1978
DOI: 10.1002/kin.550100704
|View full text |Cite
|
Sign up to set email alerts
|

On the reactivity of diethyl hydroxyl amine toward free radicals

Abstract: Diethyl hydroxyl amine is an efficient trap for alkyl, alkoxy, and peroxy radicals. The specific rate constant for the reaction of ethyl radicals (gas phase, 25"C), tert-butoxy radicals (benzene solution, 115"C), and poly (peroxystyryl) peroxy radicals (styrene solution, 50°C) were evaluated as 7.2 X lo5, 7.7 X lo7, and 2.9 X lo5 M-l-sec-', respectively. Several possible secondary reactions of the nitroxide radicals are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Oxygen and Peroxides Diethylhydroxylamine (DEHA), because of its rapid reaction with alkyl, alkoxy, or peroxy radicals or with air to produce diethyl nitroxide (446), captured interest for its potential as a combatant of photochemical smog brought about by oxidation of nitrogen oxides in the presence of hydrocarbons (eq 336) . 344,345 (C2H5)!^+ Apparently all hydroxylamines with a free hydroxyl group at nitrogen attached to one or two hydrocarbon groups is subject to air oxidation. Nitroxide formation generally required the absence of hydrogen attached to either nitrogen or the a-carbon atom.3346 Such a hindered hydroxylamine (447) is the precursor to 4,4-dimethyloxazolidine-A/-oxy (doxyl) (448) in a new preparation of the latter in four steps from 4,4-dimethyloxazoline (eq 337) .…”
Section: A Electrochemical Oxidationmentioning
confidence: 99%
“…Oxygen and Peroxides Diethylhydroxylamine (DEHA), because of its rapid reaction with alkyl, alkoxy, or peroxy radicals or with air to produce diethyl nitroxide (446), captured interest for its potential as a combatant of photochemical smog brought about by oxidation of nitrogen oxides in the presence of hydrocarbons (eq 336) . 344,345 (C2H5)!^+ Apparently all hydroxylamines with a free hydroxyl group at nitrogen attached to one or two hydrocarbon groups is subject to air oxidation. Nitroxide formation generally required the absence of hydrogen attached to either nitrogen or the a-carbon atom.3346 Such a hindered hydroxylamine (447) is the precursor to 4,4-dimethyloxazolidine-A/-oxy (doxyl) (448) in a new preparation of the latter in four steps from 4,4-dimethyloxazoline (eq 337) .…”
Section: A Electrochemical Oxidationmentioning
confidence: 99%
“…It follows from the product composition (Table 2) 28 and the initial concentration of styrene and 2 that the hydrogen transfer rate from 2 to 5 is 5 × 10 3 M -1 s -1 at 120°C. 31 Our rate constant is comparable in magnitude to primary alkyl abstracting H • from dodecane, k ) 3.5 × 10 3 M -1 s -1 at 100°C. Previous literature on H • abstraction rates from hydroxylamines is confined to the observations that t-Bu • abstracts H • from 2 1.2 times faster than from isoprene 30 and that the H • transfer rate from 2 to ethyl radicals in the gas phase at 25°C is 7.7 × 10 5 M -1 s -1 .…”
Section: Discussionmentioning
confidence: 56%
“…From the bond dissociation energy of ethylbenzene and Tempo 13 (85.4 and 71.8 kcal/mol, respectively), we calculate that this slow hydrogen transfer is exothermic by 13.6 kcal/mol. Previous literature on H • abstraction rates from hydroxylamines is confined to the observations that t -Bu • abstracts H • from 2 1.2 times faster than from isoprene and that the H • transfer rate from 2 to ethyl radicals in the gas phase at 25 °C is 7.7 × 10 5 M -1 s -1 . Our rate constant is comparable in magnitude to primary alkyl abstracting H • from dodecane, k = 3.5 × 10 3 M -1 s -1 at 100 °C …”
Section: Discussionmentioning
confidence: 57%
“…However, addition of Catalase (1000 U/ml) did not abolish the EPR signal, which was reduced only by less than 10%, indicating that oxidation of I by peroxidase is not a major process leading to the nitroxide II under our experimental conditions. Thus the rate constant for hydrogen abstraction by peroxyl radicals has been reported as k = 3 X 10 5 M _1 s _1 at 323 K from diethyl hydroxylamine [31] and as k = 5 X 10 5 M _1 s _1 at 338 K from 1 -hydroxyl-4-oxo-2,2,6,6-tetramethyl-piperidine [32]. Scheme 4 formed upon addition of SOD to the system suggested that our probe would selectively detect Superoxide in hepatic microsome preparations from mice [23], subsequent studies revealed that this is not actually the case [24].…”
Section: Mechanism Advantages and Limitationsmentioning
confidence: 99%
“…Another advantage of our probe as compared with more traditional systems is given by its peculiar chemi-For example, the ratio of the rate constant for the reaction (CH 3 ) 3 C0 1 + Et 2 N-OH over the rate of ß-cleavage for butoxyl radical at 388 K has been reported as k H /k ß = 1.4 X 10 3 M" 1 [31] and k ß can be calculated as 5.5 X 10 4 s _1 at the same temperature [33], hence as k H = 7.7 X 10 7 M _1 s -1 . However, if what one wants to obtain is a comprehensive quantitative evaluation of OSS, this factor may actually be an advantage.…”
Section: Mechanism Advantages and Limitationsmentioning
confidence: 99%